2021
DOI: 10.1007/s11695-021-05390-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Liver Recovery After Sleeve Gastrectomy and Roux-en-Y-Gastric Bypass

Abstract: Background Nonalcoholic fatty liver disease (NAFLD) is a common condition in patients with obesity. Bariatric surgery has often been proposed as a viable treatment option, but the ideal surgical procedure remains unclear. Inconsistently, reports on postoperative deterioration of liver function put further doubt on which technique to apply. Aim of this study was to assess the impact of Roux-en-Y-gastric bypass (RYGB) and sleeve gastrectomy (SG) on the postoperative recovery of liver function. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 44 publications
(67 reference statements)
2
14
0
Order By: Relevance
“…NFS was significantly reduced by LCD as well as by RYGB, which is in accordance with beneficial effects on NAFLD having been reported for bariatric surgery [ 19 , 29 ]. Appearing somewhat contradictory, mean BARD scores addressing liver fibrosis increased during 12 months of weight loss in LCD patients.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…NFS was significantly reduced by LCD as well as by RYGB, which is in accordance with beneficial effects on NAFLD having been reported for bariatric surgery [ 19 , 29 ]. Appearing somewhat contradictory, mean BARD scores addressing liver fibrosis increased during 12 months of weight loss in LCD patients.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, it appears reasonable to assume that the pronounced reduction in body fat percentage in men might be causally linked with a stronger decrease in NAFLD-related fibrosis risk. On the other hand, a recent study from Schmitz et al suggested male sex as one of several factors impeding the recovery of liver function in bariatric surgery [ 19 ]. Thus, a rather complex sexual dimorphism regarding the therapeutic impact of diet and bariatric surgery both on obesity and liver fibrosis should definitely be considered and will have to be examined in detail by further studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in severe cases, it can potentially be lethal due to the risk of associated bowel ischemia (Figure 4) and potential late risk of chronic bilioportal cholangiopathy that can lead to small bowel resection and even liver transplantation [9]. Moreover, the occurrence of PMVT is among the factors that influence early postoperative liver function capacity of patients after bariatric surgery [10]. In our survey, the most common presentation was abdominal pain in over 96% of cases, followed by nausea in almost half of cases, and vomiting in 27%.…”
Section: Discussionmentioning
confidence: 99%
“…In the NAFLD/NASH setting, LiMAx has so far been assessed in the subgroup of patients scheduled for bariatric surgery [16][17][18]: Hepatic function was lower in individuals with NASH compared to those without and in patients with increasing stages of hepatic fibrosis [16,17]. In patients with type 2 diabetes (T2D), the recovery of liver function after bariatric surgery was significantly impaired [18]. A pilot study assessing the relationship between LiMAx and elastography in a cohort with different chronic liver diseases observed a negative correlation between hepatic function and shear wave speed measured by two-dimensional time-harmonic elastography indicating that increased tissue stiffness is associated with a decreased metabolic capacity of the liver [19].…”
Section: Introductionmentioning
confidence: 99%